Bibliometric analysis of global research trends and prospects on circulating tumor DNA in colorectal cancer - Jing Pang; Pengyu Bai; Yong Zhang; Lichun Wang (Frontiers in Oncology)
BackgroundColorectal cancer (CRC) is one of the most commonly diagnosed advanced-stage malignancies worldwide and places a substantial burden on both the economic and social development of numerous countries.ObjectiveThis manuscript aims to synthesize the existing evidence and explore potential avenues for future scholarly research on ctDNA in CRC.MethodsBibliometric analyses were performed using the bibliometrix package in R, along with CiteSpace and VOSviewer software. The search was restricted to publications up to 31 March 2024, using the following terms: (“ctDNA” OR “circulating tumor DNA”) AND (“colorectal cancer” OR “colorectal tumor”) from the Web of Science Core Collection (WoSCC) database.ResultsUltimately, we identified 1,310 documents published in 353 journals authored by 7,683 researchers from 2,417 institutions across 66 countries. The USA was the most productive country. The Journal of Clinical Oncology was the most prolific, publishing 111 articles with 3,396 citations. The top five keywords were “colorectal cancer,” “circulating tumor DNA,” “acquired resistance,” “cell-free DNA,” and “plasma.” The top five cluster labels for references were “advanced cancer,” “metastatic colorectal cancer,” “liquid biopsy,” “colorectal cancer,” and “human colorectal cancer xenograft.”ConclusionsThe collaborative networks are primarily composed of highly productive authors, prestigious institutions, and leading countries. Additionally, the advancement of detection technologies, the development of standardized protocols, the exploration of circulating tumor DNA (ctDNA) dynamics in CRC, and the implementation of large-scale clinical trials for ctDNA-guided precision therapy in CRC are expected to become major research priorities in the future.